The New Challenging Program of 21st Century Women Education to Promote Peace and Harmony - Phanommas Bamrungsin (STAB Kertarajasa, 2022)
Currently, the role of women to participate and promote peace and harmony is as an essential matter and become a new challenging for them. Especially in the 21st century, women have much more opportunity to be educated, to gain more knowledge in order to improve their life and society as well as they have more beautiful chance to promote peace and harmony for well-beings. However, to be strengthen on promoting peace and harmony in the messy society and cleavage in different religions. Thus the new effective education is as a key important to cope these challenging. Therefore this paper would present the concept of new challenging program of 21st century women education to promote peace and harmony (NCPCWEPPH). The fundamental of NCPCWEPPH is to integrate knowledge of peace and harmony to higher education students’ learning courses, continue practice and cultivate themselves from the beginning of studying until graduation, furthermore learn how to promote peace and harmony in to different societies, cultures, believe and religions.